Eradicating delay in the administration of justice in African courts: a comparative analysis of South African and Nigerian courts - Hamman, Abraham J. (University of Pretoria, 2006)
Prepared under the supervision of Mr. Abraham J. Hamman, Faculty of Law, University of Western Cape, South Africa